THE EFFECT OF AUDITOR CHARACTERISTICS AND GENDER DIVERSITY ON FRAUD DETECTION - Ika Ferina; Dicky Pratama (JRAK, 2023)
Accounting fraud can occur in any company and must be detected to reduce it. This research aims at empirically investigating the effects of auditor characteristics and gender diversity on fraud detection. The population used mining companies listed on the Indonesia Stock Exchange for 2016-2020 with 205 observation data. The data analysis technique used was the Panel Data Regression Model. The results showed that auditor independence and audit report lag had a positive effect, and audit tenure and gender diversity harmed fraud detection. Additionally, auditor rotation, auditor industry specialization, and audit firm size also had not. The auditor’s independence and adequate audit period would allow the auditor to be more effective in fraud detection.